Analysis of alterations in the composition of the intestinal microbiota in frail older individuals - Chuan Zhang; Lu Gong; Shilan Luo; Lamei Yang; Xiaoli Yan (PLoS ONE, 2025)
Background Frailty is an ageing-associated geriatric syndrome that severely affects the functional status, quality of life and life expectancy of older adults. Immune dysfunction and chronic inflammation play crucial roles in frailty, and this study aimed to explore the correlation between the intestinal microbiota and frailty. Methods A cross-sectional survey was conducted using a comprehensive geriatric assessment of older individuals who underwent medical checkups at the Health Management Center from April 2023 to May 2024. A total of 672 older individuals who met the inclusion criteria were included and divided into a healthy control group and a frail case group. Clinical data, as well as blood and stool samples, were collected. The data from the two groups were analysed with 16S rRNA sequencing in 20 and 30 cases, respectively. SPSS 25.0 was used for statistical analysis. Results There were significant differences in income, smoking, and globulin levels between the two groups, while there were no differences in age or sex. There was no significant difference in the abundance or species evenness of intestinal bacteria between the two groups. However, the abundance of accessory bacteria, bifidobacteria, and Escherichia coli in the frail group was greater than that in the control group. Specifically, Escherichia-Shigella was significantly upregulated and fit well into the prediction model of frailty. Conclusion The gut microbiota of frail older individuals underwent significant changes in structural composition, and the presence of Escherichia-Shigella may be a diagnostic marker for debilitating diseases. These findings provide an essential clinical reference value for developing methods for preventing or alleviating frailty based on specific microbial communities.